Soil Bacterial Communities and Diversity in Alpine Grasslands on the Tibetan Plateau Based on 16S rRNA Gene Sequencing - Jiang, Hongmao; Chen, Youchao; Hu, Yang; Wang, Ziwei; Lu, Xuyang (Frontiers in Ecology and Evolution, 2021)
The Tibetan Plateau, widely known as world’s ‘Third Pole’, has gained extensive attention due to its susceptibility to climate change. Alpine grasslands are the dominant ecosystem on the Tibetan Plateau, albeit little is known about the microbial community and diversity among different alpine grassland types. Here, soil bacterial composition and diversity in the upper soils of five alpine grassland ecosystems, alpine meadow, alpine steppe, alpine meadow steppe, alpine desert and alpine desert steppe, were investigated based on the 16S rRNA gene sequencing technology. Actinobacteria (46.12%) and Proteobacteria (29.67%) were the two dominant soil bacteria at the phylum level in alpine grasslands. There were significant differences in the relative abundance at the genus level among the five different grassland types, especially for the Rubrobacter, Solirubrobacter, Pseudonocardia, Gaiella, Haliangium and Geodermatophilus. Six alpha diversity indices were calculated based on the operational taxonomic units (OTUs), including Good's coverage index, phylogenetic diversity whole tree index, Chao1 index, observed species index, Shannon index, and Simpson index. The Good's coverage index value around 0.97 for all the grassland types in the study area, meaning the soil bacteria samplings sequenced sufficiently. No statistically significant difference was shown in other diversity indices' value, indicating the similar richness and evenness of soil bacteria in these alpine grasslands. The beta diversity, represented by Bray–Curtis dissimilarity and the non-metric multidimensional scaling (NMDS), showed that OTUs were clustered within alpine grasslands, indicating a clear separation of soil bacterial communities. In addition, soil organic matter (SOM), total nitrogen (TN), total phosphorus (TP), pH, and soil water content (SWC) were closely related to the variations in soil bacterial compositions. These results indicated that soil bacterial taxonomic compositions were similar, while soil bacterial community structures were different among the five alpine grassland types. The environmental conditions, including SOM, TN, TP, pH and SWC, might influence the soil bacterial communities on the Tibetan Plateau.